The effect of in-hospital acquired thrombocytopenia on the outcome of patients with acute coronary syndromes: A systematic review and meta-analysis. Issue 147 (November 2016) - Oikonomou, Evangelos K.; Repanas, Theodoros I.; Papanastasiou, Christos; Kokkinidis, Damianos G.; Miligkos, Michael; Feher, Attila; Gupta, Dipti; Kampaktsis, Polydoros N.
Abstract: Background: In-hospital acquired thrombocytopenia (TP) is relatively common among patients hospitalized with acute coronary syndromes (ACS). However, its effect on short-term and long-term outcomes has yet to be reviewed systematically. Methods: We conducted a systematic review and meta-analysis of clinical studies assessing the relationship between new-onset in-hospital TP and adverse outcomes among ACS patients. MEDLINE, Scopus and the Cochrane Library were searched for eligible studies published before March 20, 2016. Results: Ten studies reporting on a total of 142, 161 ACS patients were identified. 8133 patients showed evidence of new-onset TP during the course of their hospitalization. Compared with patients with normal platelet counts, patients with new-onset TP had a prolonged in-hospital stay, significantly higher risk of both short-term mortality (< 30 days) (Odds ratio (OR) [95% confidence interval (CI)]: 5.58 [3.63–8.57]) and late death (6 months to 1 year) (OR [95% CI]: 3.45 [2.35–5.07]), as well as a significantly higher risk of major bleeding events in the first 30 days (OR [95% CI]: 6.93 [5.13–9.38]). In addition, risk for other secondary cardiovascular endpoints, including recurrent myocardial infarction, stroke, in-hospital heart failure, stent thrombosis and unplanned revascularization was also significantly higher in the TP versus the no TP group. Conclusions: Development of TP during the in-hospital management of ACS patients is a significant predictor of both short- and long-term adverse events, including mortality. In the light of this evidence, clinicians should be cautious and closely monitor abnormal platelet counts that present early following an ACS. Graphical abstract: Highlights: In-hospital acquired thrombocytopenia (IATP) is relatively common in ACS patients. IATP is a significant predictor of both early and late mortality. IATP is a risk factor for both hemorrhagic and thrombotic adverse events. Physicians should monitor closely platelet counts in ACS patients. Further research is needed on the optimal management of ACS patients with IATP.